Aspirin Effect on Staphylococcus aureus—Platelet Interactions During Infectious Endocarditis - Hannachi, Nadji; Habib, Gilbert; Camoin-Jau, Laurence (Frontiers in Medicine, 2019)
Infectious endocarditis (IE) is a rare disease associated with high mortality and morbidity rate. The platelet–bacterial interaction presents the cornerstone of the development of endocardial vegetation. The epidemiology of IE has undergone profound changes between the last and the new decade, with Staphylococcus aureus becoming the main incriminated species. Despite improvements in antibiotic and surgical therapies, embolic disorders remain highly associated with IE that can be fatal. Antiplatelet drugs have been widely proposed to overcome embolic events associated with IE. This proposal has been supported by numerous in vitro, experimental, and clinical studies. However, other studies have yielded conflicting results. In this review, we focus on the effect of aspirin on the genesis of S. aureus endocarditic vegetation, as well as on the management of embolic and hemorrhagic events related to it, starting by its influence on the platelet–bacteria interaction.